A field experiment on bargaining for seed reveals discrimination against women agripreneurs - Van Campenhout, Bjorn; Nabwire, Leocardia (CGIAR, 2023)
This policy note summarizes results from a Lab-in-the-field experiment1 in eastern Uganda, where a representative sample of 760 smallholder maize farmers were given the opportunity to bargain over a bag of maize seed from either a male or female seller. Specifically, we test whether the gender of the seed seller impacts the seed buyer’s negotiation strategies and the eventual outcomes in bilateral price negotiations. The findings reveal that buyers confronted with a female seller were less likely to accept the seller’s initial offer price and responded with a lower counter price compared to farmers faced with a male seller. Negotiations, on average, took one additional round when the seller was a woman and resulted in a transaction price that was almost 9 percent lower. These results relate to previous research with agro-input dealers in Uganda which showed that female managed/owned agro-input shops are perceived less favorable in terms of quality of seed sold and price competitive ness. Policies and programs working to advance women’s empowerment through agribusiness need to recognize these gendered biases, and increase investment in public campaigns, extension and training to change attitudes towards women entrepreneurs.